Penerapan Layanan Bimbingan Kelompok untuk Meningkatkan Motivasi Belajar Siswa Kelas VIII - Hermawan, Muhammad Fadhillah; Dartina, Vina (Jurnal Dimamu, 2024)
The research that has been carried out aims to obtain an informative description of learning motivation, differences in behavior of students who have high and low learning motivation, and to find out the group guidance services provided by guidance and counseling teachers in increasing the learning motivation of class VIII students at SMP Negeri 3 Cileunyi. The COVID-19 pandemic has changed the mobility of students who are accustomed to learning face-to-face and interacting at school, then they are required to be able to quickly adapt to the online learning system and limit activities outside the home. After the COVID-19 pandemic ended, students again had to adapt to changes in the face-to-face learning system in the classroom as usual so that it had an impact on the differences in learning motivation shown by each student. As an effort to increase student learning motivation, especially in Class VIII, guidance and counseling teachers provide group guidance services so that students can increase their learning motivation through the process of group interaction. This study used a qualitative method (qualitative research), with a case study approach. Data collection techniques through observation, in-depth interviews, and documentation. Informants in this study were school principals, homeroom teachers, and guidance andcounseling teachers at SMP Negeri 3 Cileunyi. The results of this study showed that each student has a variety of learning motivation, namely high and low. In an effort to increase student learning motivation, the principal, guidance and counseling teachers, and homeroom teachers have an active role. The principal's role is to provide direction and work together with all teaching staff and extracurricular coaches, the homeroom teacher's role is to pay attention and hold question and answer sessions and discussions with rewards so that students are motivated to learn. Meanwhile, the guidance and counseling teacher has the role of implementing counseling and guidance services. guidance and counseling teachers carry out group guidance by means of group discussions, role playing, playing games, and providing information through video shows. Group guidance topics presented are about time management, Children's responsibility for their role as student adolescents, as well as how to learn effectively and understand the reasons for learning difficulties.